EFEKTIVITAS PENGGUNAAN APLIKASI SISKEUDES DALAM PELAPORAN KEUANGAN DI DESA PERMISAN KECAMATAN JABON - Maya Setiowati; Isna Fitria Agustina (Halu Oleo University, 2024)
The aim of this research is to measure the effectiveness of using the Siskeudes application in financial reporting in Permisan Village. This research uses qualitative methods. This type of research is descriptive qualitative. The data collection technique uses observation at the research site, then conducting interviews with informants, and carrying out documentation. The results of research based on the theory of effectiveness put forward by Duncan in Steers show that the use of the Siskeudes application in the Permisan Village Government, Jabon District is quite effective because all stages have been carried out as they should. However, there are several obstacles that often occur, namely internet network problems which can interfere with village financial reporting via the Siskeudes application. It is hoped that evaluations in the use of the Siskeudes application will be carried out regularly to realize the success of the Siskeudes application.